The Jurisdiction Analysis of Criminal Acts of Fraud & Embedding in the Buying of Fish - Faiz Harinda Pratama; Ira Alia Maerani; Djunaedi Djunaedi (Universitas Islam Sultan Agung, 2022)
This study aims to identify and analyze the investigation of criminal acts of fraud and embezzlement in the sale and purchase of fish at the Batang Police Resort. The approach used is sociological juridical. Collecting data through interviews, literature studies and documentation studies. The study concluded that the investigation of criminal acts of fraud and embezzlement in the sale and purchase of fish at the Batang Police Resort was based on the Criminal Procedure Code, the National Police Chief Regulation Number 6 of 2019 and the Republic of Indonesia Police Circular Number: SE/8/VII/2018. In the investigation of the crime, the investigator seeks a peaceful settlement of the case through a restorative justice approach with a view to obtaining a fair settlement for both parties. On the one hand, the victim gets a recovery from the loss and on the other hand the suspect can be released from criminal prosecution.This study aims to identify and analyze the investigation of criminal acts of fraud and embezzlement in the sale and purchase of fish at the Batang Police Resort. The approach used is sociological juridical. Collecting data through interviews, literature studies and documentation studies. The study concluded that the investigation of criminal acts of fraud and embezzlement in the sale and purchase of fish at the Batang Police Resort was based on the Criminal Procedure Code, the National Police Chief Regulation Number 6 of 2019 and the Republic of Indonesia Police Circular Number: SE/8/VII/2018. In the investigation of the crime, the investigator seeks a peaceful settlement of the case through a restorative justice approach with a view to obtaining a fair settlement for both parties. On the one hand, the victim gets a recovery from the loss and on the other hand the suspect can be released from criminal prosecution.Keywords: Embezzlement; Fish; Fraud; Investigation; Transaction.